Psychoeducational programs in psychiatry – possibilities and limitations of their application - Majewicz, Piotr (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
Psychoeducation is currently used in many areas of life, including psychiatry. It is difficult to imagine the modern process of treating people with mental disorders without the use of psychoeducation as a necessary, permanent element of this process, in addition to pharmacotherapy and psychotherapy. Psychoeducational programs are used primarily in the treatment of people with schizophrenia spectrum disorders and those suffering from bipolar affective disorder (BPAD). These programs are not only directed to the patient, but they are also addressed to their family members and friends. The article presents the possibilities of using selected psychoeducational programs, including the PEGASUS program, the Barcelona Psychoeducation Program and the Krakow Program for People with BPAD, as well as limitations of their application. The goals of these programs, their structure and effectiveness were also presented.